In Vitro Validation of Antiparasitic Activity of PLA-Nanoparticles of Sodium Diethyldithiocarbamate against Trypanosoma cruzi - Johny Wysllas de Freitas Oliveira; Mariana Farias Alves da Silva; Igor Zumba Damasceno; Hugo Alexandre Oliveira Rocha; Arnóbio Antônio da Silva Júnior; Marcelo Sousa Silva (Pharmaceutics, 2022)
Trypanosoma cruzi is a protozoan parasite responsible for Chagas disease, which affects millions around the world and is not treatable in its chronic stage. Sodium diethyldithiocarbamate is a compound belonging to the carbamate class and, in a previous study, demonstrated high efficacy against T. cruzi, showing itself to be a promising compound for the treatment of Chagas disease. This study investigates the encapsulation of sodium diethyldithiocarbamate by poly-lactic acid in nanoparticles, a system of biodegradable nanoparticles that is capable of reducing the toxicity caused by free DETC against cells and maintaining the antiparasitic activity. The nanosystem PLA-DETC was fabricated using nanoprecipitation, and its physical characterization was measured via DLS, SEM, and AFM, demonstrating a small size around 168 nm and a zeta potential of around −19 mv. Furthermore, the toxicity was determined by MTT reduction against three cell lines (VERO, 3T3, and RAW), and when compared to free DETC, we observed a reduction in cell mortality, demonstrating the importance of DETC nanoencapsulation. In addition, the nanoparticles were stained with FITC and put in contact with cells for 24 h, followed by confirmation of whether the nanosystem was inside the cells. Lastly, the antiparasitic activity against different strains of T. cruzi in trypomastigote forms was determined by resazurin reduction and ROS production, which demonstrated high efficacy towards T. cruzi equal to that of free DETC.